Drawing And Journaling To Reduce Auditory Hallucination In A Schizoaffective Patient At West Java Mental Hospital: Case Report - Syifa Nada Muslimah; Imas Rafiyah; Hendrawati Hendrawati (Jurnal Multidisiplin, 2026)
Schizoaffective disorders is a mental disorder characterized by a combination of psychotic and affective symptoms, one of which is auditory hallucinations. Untreated hallucinations can interfere with daily functioning and may pose risks to the individual and others. The management of hallucinations is not limited to pharmacological therapy but can also be supported by complementary interventions such as drawing and journaling. This study aimed to evaluate the implementation of drawing and journaling interventions in reducing auditory hallucinations in a patient with manic-type schizoaffective disorder. This study employed a clinical case report design with a descriptive approach involving a 23-year-old male patient diagnosed with schizoaffective disorder, manic type, at the West Java Provincial Mental Hospital. The interventions were conducted over four consecutive days, with a duration of 15–20 minutes per session. Data were collected through observation and interviews based on the Mental Health Nursing Care Standards and were analyzed using a qualitative descriptive approach. The results showed a gradual decrease in the frequency and intensity of hallucinations, from 5–6 times per day to complete absence in the final session. In addition, the patient demonstrated improved focus, cooperativeness, and ability to express emotions. The combination of drawing and journaling interventions was effective in reducing hallucinations by helping the patient divert attention, express emotions, and enhance self-awareness. These interventions are effective as complementary therapies in reducing auditory hallucinations and improving psychological well-being in patients with schizoaffective disorder.